MANAGEMENT STRATEGY FOR ISLAMIC EDUCATION INSTITUTIONS IN IMPROVING DISCIPLINE CHARACTER - Rosidi, Ahmad; Juan, Firda (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2023)
Discipline is obedience to respect and implement a system that requires people to comply with decisions, orders, and regulations that apply. Islam teaches us to pay attention to and use disciplinary values in everyday life to build better community life. This study aims to determine the discipline techniques and strategies of SD Al-Furqon Jember students. The high level of student discipline is due to the high motivation of teachers towards students about the importance of discipline. In addition, sanctions against students who do not comply with the rules are also a motivating factor for students always to instill discipline. The research method used is a descriptive qualitative method and collects data using the form of observation, interviews, and documentation. The study results showed that (1) the disciplinary techniques of SD A-Furqon students were excellent, and they had to continue to improve the discipline of students (2) the strategy of SD AL-Furqon teachers in improving student learning discipline used a Personal Approach, Group Approach such as advising if it is too late in the prayer congregation, and Character and Moral Guidance.